Handwriting the way to teach it - Sassoon, Rosemary; Savage, Pat. (London : Paul Chapman, 2003)
Covering all aspects of the subject, Sassoon presents examples and imaginative ideas to make learning to write more effective and interesting for children and for teachers. This edition includes material on problems which children can have with handwriting, and how to diagnose and remedy them.
Previous ed.: Cheltenham: Thornes, 1990.
Includes index.
Illustrations by Pat Savage.
Description based on print version record.
Keywords: Penmanship -- Study and teaching